Do audit committee characteristics improve financial reporting quality in emerging markets? Evidence from Iran - Safari Gerayli, Mehdi (2021)
Purpose The purpose of this study is to investigate the association between certain audit committee characteristics like independence and financial expertise with financial reporting quality (FRQ) of the firms listed on the Tehran Stock Exchange (TSE). Design/methodology/approach The sample includes the 558 firm-year observations from companies listed on the TSE during the years 2012-2017, and the study's hypotheses were tested using multivariate regression model based on panel data. Findings The authors find that audit committee independence has no significant effect on corporate FRQ, whereas audit committee's financial expertise significantly improves firms' FRQ. In other words, higher financial expertise of an audit committee can lead to an increase in its FRQ. The findings of the study are robust to alternate measures of FRQ, individual analysis of the research hypotheses for each year and endogeneity problem. Originality/value To the best of the authors' knowledge, this is the first study to analyze the association between audit committee characteristics and FRQ in emerging capital markets, and so, the findings of the study not only extend the extant theoretical literature concerning the audit committee in developing countries including emerging capital market of Iran but also help investors, managers, capital market regulators, policymakers and audit profession regulators to make informed decisions.